UNIVERSALITAS KETAUHIDAN TUHAN: (Pembacaan Al-Qur’an Pra-Kanonisasi Angelika Neuwirth Terhadap Surat Al-Ikhlas) - Roudhotul Jannah (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2019)
This article is about Angelika Neuwirth’s thought, dialectical of Qur’anic interpretation. She offer new view to understanding of Qur’an’s meaning. Neuwirth encourage to reunderstanding Qur’an post-canonization (a written text) with pre-canonization method (oral communication), as in Surat Al-Ikhlas. Accourding Neuwirth, Surat Al-Ikhlas responded from tradition and civilization of Arabic region earlier. An example أَحَدٌ (Q.112:1) is similiar meaning with “ehad” in Ibrani language. That’s mean usage أَحَدٌ had purpose to negotiation strategy and universality of faith. therefore Islamic religion has mission to combine all ideology of faith become unity universality. Neuwirth encourages to refer to the other holy scripture for adding comprehensive information and objective data.